2014
DOI: 10.1515/zpch-2014-0636
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbon Nanowalls and Few-Layer Graphene Sheets on Transparent Conductive Substrates

Abstract: Abstract:We report on the growth of carbon nanowalls and few-layer graphene sheets on glass substrates coated with different transparent conductive oxides or gold. The growth is accomplished by a capacitively-coupled radio-frequency plasma-enhanced chemical vapor deposition setup with a gas mixture of C 2 H 2 , H 2 , and Ar or He. This system allows the synthesis of thin vertical carbon nanosheets without catalyst at mild reaction conditions due to the low plasma density, which is preferable for sensitive subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…The final goal was to establish a geometry as it is typical for carbon nanowalls. 26 For carbonnanowall formation, it has been shown that grain boundaries play a crucial role, according to Zhu et al 48 During the first few minutes of the synthesis, the formation of a 1-15 nm thick layer of graphitic sheets is described, which grows parallel to the substrate. Once a sufficient level of force develops at the grain boundaries, vertical, diffusion-controlled growth is enabled.…”
Section: Pecvd Of Tin-sulfide Nanowallsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final goal was to establish a geometry as it is typical for carbon nanowalls. 26 For carbonnanowall formation, it has been shown that grain boundaries play a crucial role, according to Zhu et al 48 During the first few minutes of the synthesis, the formation of a 1-15 nm thick layer of graphitic sheets is described, which grows parallel to the substrate. Once a sufficient level of force develops at the grain boundaries, vertical, diffusion-controlled growth is enabled.…”
Section: Pecvd Of Tin-sulfide Nanowallsmentioning
confidence: 99%
“…A very prominent example for nanowalls are carbon nanowalls. 26,27 These structures are typically synthesized via plasma-enhanced chemical vapor deposition (PECVD). In the past, PECVD has already been used for the deposition of tin sulfide.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis was performed in a custom-built capacitively coupled radio-frequency (13.56 MHz) plasmaenhanced CVD (CC-PECVD) setup. 15 A gas mixture of C 2 H 2 , H 2 , and He with flow rates of 10, 80, and 70 standard cubic centimeters per minute (sccm), respectively, were used. The substrate temperature of 650 °C was controlled by a resistively heatable stage that also acts as counter electrode.…”
Section: Synthesis Of Flg Sheetsmentioning
confidence: 99%
“…Recently we have shown that these highly conductive carbon nanostructures can be prepared with a very high specific surface area. 15 Here, we used a high-voltage electrochemical deposition technique to prepare Pd nanoparticles directly on the FLG sheets to ensure that every catalyst particle has electrical contact. This method led to controllable catalyst loadings showing a homogenous arrangement of small particles, which is unprecedented in literature so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation